2012
DOI: 10.5209/rev_sjop.2012.v15.n3.39387
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic and Non-Symbolic Number Magnitude Processing in Children with Developmental Dyscalculia

Abstract: The aim of this study was to evaluate if children with Developmental Dyscalculia (DD) exhibit a general deficit in magnitude representations or a specific deficit in the connection of symbolic representations with the corresponding analogous magnitudes. DD was diagnosed using a timed arithmetic task. The experimental magnitude comparison tasks were presented in non-symbolic and symbolic formats. DD and typically developing (TD) children showed similar numerical distance and size congruity effects. However, DD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 64 publications
2
16
0
1
Order By: Relevance
“…Note the statistically significant and high correlations found between nonsymbolic and symbolic numerical comparison tasks and mental arithmetic remain, despite the contribution of domain-general cognitive processes to performance was controlled for. These results are consistent with previous reports on children with low math achievement exhibiting significant differences in basic numerical processing when compared to controls, even when controlling for working memory processes (Castro et al, 2012;Wong et al, 2015). Nevertheless it is worth mentioning the analysis controlling for the effect of verbal and visuospatial working memory processes in the sample presented here contributes new relevant evidence in typically developing children, not available in previous reliability/convergent validity studies, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Note the statistically significant and high correlations found between nonsymbolic and symbolic numerical comparison tasks and mental arithmetic remain, despite the contribution of domain-general cognitive processes to performance was controlled for. These results are consistent with previous reports on children with low math achievement exhibiting significant differences in basic numerical processing when compared to controls, even when controlling for working memory processes (Castro et al, 2012;Wong et al, 2015). Nevertheless it is worth mentioning the analysis controlling for the effect of verbal and visuospatial working memory processes in the sample presented here contributes new relevant evidence in typically developing children, not available in previous reliability/convergent validity studies, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies involving children exhibiting typical development of numerical processing or children with arithmetic learning disabilities support in a similar way the relevance of nonsymbolic skills as predictors of subsequent arithmetic performance (Halberda et al, 2012;Libertus et al, 2011;Mussolin et al, 2010;Reigosa-Crespo et al, 2013;Wong, Ho, & Tang, 2015). In contrast, other studies highlight symbolic and mapping skills preponderant role as predictors of arithmetic success in children (Castro et al, 2012;De Smedt & Gilmore, 2011;Landerl & Kölle, 2009;Lonnemann et al, 2011;Rousselle & Noel, 2007;Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013).…”
mentioning
confidence: 93%
“…Previous findings about non-symbolic magnitude processing are inconclusive (Price et al, 2007; Mussolin et al, 2010b; Piazza et al, 2010; Kucian et al, 2011b; Castro Cañizares et al, 2012; Landerl, 2013; Skagerlund and Träff, 2014). In addition, it has been shown that numerosity is not processed independently from its continuous visual variables (diameter, total surface, density; Gebuis and Reynvoet, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies also reported a low ANS acuity in dyscalculia, indexed by impairments in dot comparison tasks, where DD seem to have a 5 year-delay along the typical developmental trajectory [28][29][30][31][32]. These findings, however, are not undisputed, since using similar (but not identical) dots comparison tasks, some researchers did not find differences between DD and controls [33][34][35]. Moreover, there is an ongoing debate on the factors underlying the DD poor performance in this task: some reported evidence that it is determined by a non-specific deficit in a general inhibitory system [36], while others failed at replicating it [37].…”
Section: Introductionmentioning
confidence: 89%